THE MODEL OF BRIMOB-POLRES RELATIONSHIP: HUMAN RESOURCES MANAGEMENT PERSPECTIVE - Cahya Dwi Sancaka, Hendri; Sarpan, Sarpan (Dinasti Publisher, 2021)
The low image of the regional police, which is still relatively poorly known as an institution for protecting, protecting and serving the community is indicated by the service value provided by the regional police which is still lacking in handling riots and riots as well as the relative lack of relationship between Brimob-Polres and regional police. The purpose of this research is to describe the Correlation of Brimob-Polres, Service Value, Police Image, and to test the magnitude of the influence of Brimob-Polres Relationship to Service Value and its implications for Regional Police Image. The method used is descriptive survey method and explanatory survey. The type of investigation in this study is causality. The unit of analysis for the Head of Polres in the West Java Regional Police with a sample of 35 Polres Heads. The time horizon in this study is cross sectional and the analysis method used is the frequency distribution and path analysis. Based on the results of research and discussion, it can be found that the correlation between Brimob and Polres of West Java Regional Police is relatively high, the value of police services in the West Java area is relatively high,the image of the regional police is relatively high.Brimob-Polres relationship has an effect on the value of service, the value of police service has an effect on the image of the police, the relationship between Brimob and Polres and the value of service simultaneously affects the image of the police.